School-based assessment implementation: The primary school teachers voices - Hashim Z.; Aziz A.D.A.; Di S.; Zakaria A.R.; Baharun H. (CRC Press/Balkema, 2024)
Malaysian education assessment system is currently undergoing some changes both at primary and secondary school levels. Bringing in the School-Based Assessment (SBA) practice into the existing examination-oriented system is seen as a great challenge to the stakeholders. The aim of such implementation is to have a more holistic and less examination-oriented assessment for the students along with promoting assessment for learning. The implementation of SBA at primary school level began in 2011, whereas the implementation at secondary school level began in 2012. Since its implementation, the stakeholders, including teachers, students, parents, and non-profitable organizations, have raised their concerns over what methods and how the assessments are going to be administered, evaluated and reported. Since the implementation is considered new and little research is carried out to date on SBA in Malaysia, it is necessary to look at the issues related to the SBA implementation. Such research would help in expanding the body of literature in the field and, most importantly, it would help to acknowledge the existence of concerns by the community of practice in practicing SBA. This study is also seen as a platform to identify measures for improving the assessment practice by means of reflecting on its current practice. 2016 Taylor and Francis Group, London.